Denture-induced fibrous hyperplasia with minor salivary gland changes - A case report - Chandrasekar Muthulakshmi; Shruthi Subramanian; Shyam Sharma Ji; Sirenjivi Rengabasiyam; Shwetha Meenakshi Sundaram; Bose Divya (Wolters Kluwer Medknow Publications, 2021)
Denture-induced fibrous hyperplasia or epulis fissuratum refers to reactive tissue alteration occurring in response to trauma and chronic irritation due to the badly fitted prosthesis. Pathologic changes observed in the oral mucosa may vary depending on the severity of trauma to the mucosa. Trauma to minor salivary glands caused by the impingement of denture flanges can result in chronic sialadenitis. In this article, we discuss a case of denture-induced fibrous hyperplasia with prominent minor salivary gland changes in a Male patient of age 63 years.